Tubal plasty General Honorio Delgado Hospital of Arequipa. - Lozada S., Benigno (2015)
The sterility of women, has been and remains an issue of major decisions in the life of the woman. Primary infertility and secondary are often inquiries we receive, medical specialty, because of the important role it plays in the lives of couples, many consider this as essential to the stability of the home and therefore the couples who consider peremnización or family life, with own children and not with others.